Ethnic disparities in metabolic dysfunction-associated steatotic liver disease and clinical outcomes - Miyatani, Yusuke; Ogawa, Aoi; Sempokuya, Tomoki; Tran, Chuong; James, Davis; Seto, Todd; Shikuma, Cecilia; Kuwada, Scott K. (Frontiers in Endocrinology, 2026)
BackgroundWhile metabolic dysfunction-associated steatotic liver disease (MASLD) has become increasingly prevalent worldwide, multi-ethnic differences within a shared geography and lifestyle, have not been fully examined. What remains poorly characterized are the clinical outcomes for ethnic minorities in the U.S., particularly Asians and Native Hawaiian and Pacific Islanders (NHPI), compared with White people/persons/person.MethodsAdults (aged ≥18 years) diagnosed with MASLD between January 2008 and December 2018 were identified in the TriNetX national database using the ICD-10 codes and followed outcomes through August 2025. Propensity score matching was conducted to compare Asians and NHPI with White people/persons/person with MASLD, adjusting for age, gender, body mass index, hypertension, type 2 diabetes, hyperlipidemia, and smoking status. Hazard ratios (HR) with 95% confidence intervals were estimated for the major outcomes: all-cause mortality, cirrhosis, and hepatocellular carcinoma (HCC). The effects of extrahepatic diseases related to metabolic diseases, such as myocardial infarction (MI), heart failure (HF), chronic kidney disease (CKD), and non-HCC cancer, were examined in the analyses.ResultsA total of 188,328 White, 14,475 Asian, and 2,390 NHPI patients living in the U.S. (United States of America) with MASLD were identified with a median follow-up of over 8 years. After propensity score matching, Asian and NHPI demonstrated significantly lower rates of cirrhosis than White people/persons/person. In Asians, the risk of HCC increased with longer follow-up period, and with ≥5 years of follow-up, HCC risk significantly exceeded that of White people/persons/person. Asians had lower rates of CKD, MI, HF, and non-HCC cancers than White people/persons/person. NHPI had a significantly lower rate of non-HCC cancers but a higher risk of CKD compared with White people/persons/person. All-cause mortality was lower among Asians, but not in NHPI, compared with White people/persons/person.ConclusionsIn a large, multiethnic U.S. cohort of MASLD, Asians and NHPI showed distinct outcome profiles. Ethnicity-tailored MASLD management strategies should be further explored.